The Effect of Outcome vs. Process Accountability-Focus on Performance: A Meta-Analysis - Sharon, Ira; Drach-Zahavy, Anat; Srulovici, Einav (Frontiers in Psychology, 2022)
Abstract Background: The foundation of a safe practice is accountability, especially outcome- rather than process-focused accountability, particularly during pandemics such as COVID-19. Accountability is an essential behavior that promotes congruence between nursing actions and standards associated with quality of care. Moreover, the scant research examining whether one accountability focus is superior in motivating humans to better task performance yields inconclusive results. Aims: Systematically examine the effect of an outcome- versus process-accountability focus on performance and identify any moderating variables. Design: Systematic review and meta-analysis. Data sources: PsycINFO, Medline, PubMed, Scopus, and CINAHL databases, with all publications to November 2020. Review methods: A systematic search using Systematic Reviews and Meta-Analyses (PRISMA) guidelines was performed. Statistical analysis and forest plots were performed using MetaXL 5.3. Heterogeneity was presented using I2 statistics and Q tests, and possible publication bias was assessed with a Doi plot and the LFK index. Results: Seven studies representing nine experiments involving 1,080 participants were included. The pooled effect of the nine experiments on task performance failed to show significant differences (mean = -0.09; 95% Confidence Interval [95%CI]: -0.21, 0.03), but a significant moderating effect of task complexity was demonstrated. Specifically, outcome accountability exerts a beneficial effect in complex tasks (mean = -0.48 [95%CI: −0.62, -0.33]) whereas process accountability improves the performance in simpler tasks (mean = 0.96 [95%CI: 0.72, 1.20]). Conclusions: These findings demonstrated that accountability focus by itself cannot serve as a sole motivator of better performance, because task complexity moderates the link between accountability focus and task performance. Outcome accountability exerts a beneficial effect for more-complex tasks, whereas process accountability improves the performance of simpler tasks. These findings are crucial in nursing, where it is typically assumed that a focus on outcomes is more important than a focus on processes.